Administrative and Legal Mechanism for Ensuring the Rights of Civil Servants in Ukraine and the Developed Countries of the World - Serbyn, Ruslan; Zelenko, Inna; Kiselyova, Elena; Voloshyna, Maryna; MykhaylovsʹkaYevheniya (Cuestiones Políticas, 2020)
The relevance of this article is due to the ambiguity of the situation of trade unions in Ukraine and the lack of an effective mechanism for the protection of the rights of public officials, which directly influences the development of the state as democratic and legal. The objective of the article is to analyze the state of activity and functioning of the trade union movement in the public administration, to: describe deficiencies in these activities and identify ways to extrapolate positive international experiences in the matter to Ukraine. The main methods used were the general methods of scientific and specific research, including the methods of logic, analysis and comparison of the sources collected. By way of conclusion, the results of this study highlight the problems of union functioning together with the peculiarities in the civil service, therefore, it is proposed to amend the current legislation of Ukraine in order to protect the social and labor rights of public officials. The importance of the results obtained is further reflected in the fact that this study can serve as a basis for outlining future changes to Ukraine’s current legislation on the functioning of trade unions in the civil service.